Why (not) cooperate? A cognitive model of farmers' intention to join producer groups in Romania. Issue 1 (2nd January 2018) - Möllers, Judith; Traikova, Diana; Bîrhală, Brînduşa Ana-Maria; Wolz, Axel
ABSTRACT: After the breakdown of the communist regime in Romania, collective farms were replaced by a large number of small-scale private farms. Although cooperation seems to be a favourable choice for these smallholders, it did not develop as perhaps expected. This article explores the factors that determine the formation of the intention of Romanian vegetable farmers to join marketing cooperatives in the form of so called producer groups. Our theoretical framework refers to Ajzen's Theory of Planned Behaviour, which we model with a structural equation model. We identified as main intention drivers the expectation for better prices and easier access to capital. Perceived family support is another significant factor. The level of distrust is high. Although our trust variable is not significant as a predictor of the intention to cooperate in the model, we find qualitative indications that trust plays a role when the intention is translated into actual behaviour.